PRELIMINARY SURVEY OF HERPETOFAUNA IN UNIVERSITAS SEBELAS MARET AREA - Iman Akbar Muhtianda; Mei Lailasari; Ayu Astuti (Konservasi Hayati, 2022)
Indonesia is an archipelago country located in South-East Asia and have high numbers in species biodiversity and ecosystem variations, thus Indonesia become an area with high biodiversity serving function. Amphibians and reptiles also exist in Indonesia. Herpetology comes from Greek which consist of “herpein” means “to creep”, and “-logia” means “knowledge”, which together can be translate as a discipline of zoology that focused in amphibians and reptiles (herpetofauna). Amphibians and reptiles does not share same taxonomic group but they are studied together because they are ectotherm and poikilothermic animal. For this shared similar character hence it influence their behavior and metabolism, so they would studied with similar method in one discipline. Amphibians and reptiles are widespread across the globe in wide variety of habitat, with some limitation around earth poles, from mountain to sea. They play various roles in ecosystem from first consumer to third consumer, and can act as bioindicator, pest controller, or even recreational target for hunting. This preliminary survey was conducted in Universitas Sebelas Maret, Surakarta, Central Java, Indonesia in 13-15 November 2020 between 20:00 – 22:00 in Western Indonesian Time (GMT +7). The method was Road Cruising combined with Visual Encounter Survey. Data processed using DNRGPS and QGIS version 3.10.14. and presented in tables for species and its amount, and in map for location findings. The species encountered consist of three species of amphibians namely; Duttaphrynus melanostictus, Kaloula baleata, and Polypedates leucomystax, and four species of reptiles namely; Calotes versicolor, Gekko gecko, Hemidactylus frenatus, and Hemidactylus platyurus.